2018
DOI: 10.3390/nu10091319
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG in the Primary Prevention of Eczema in Children: A Systematic Review and Meta-Analysis

Abstract: Current guidelines recommend the use of probiotics to reduce the risk of eczema. It remains unclear which strain(s) to use. We systematically evaluated data on the efficacy of Lactobacillus rhamnosus GG (LGG) supplementation prenatally and/or postnatally for the primary prevention of eczema. The Cochrane Library, MEDLINE, and EMBASE databases were searched up to August 2018, with no language restrictions, for systematic reviews of randomized controlled trials (RCTs) and RCTs published afterwards. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…Lastly, the use of a specific probiotic strain may not lead to reproducible results, as the manufacturing environment and processing of the product, as well as the matrix, may have an effect on the efficacy of the bacterial strain studied. Indeed, this may be the reason why one RCT has shown that L rhamnosus GG is efficacious in the primary prevention of allergy, while later studies were not able to replicate these results, including a study done in a different country with the exact same methodology …”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the use of a specific probiotic strain may not lead to reproducible results, as the manufacturing environment and processing of the product, as well as the matrix, may have an effect on the efficacy of the bacterial strain studied. Indeed, this may be the reason why one RCT has shown that L rhamnosus GG is efficacious in the primary prevention of allergy, while later studies were not able to replicate these results, including a study done in a different country with the exact same methodology …”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasize that the recommendations are conditional and depend on the results of the further research. Recently, Szajewska and Horvath published a meta-analysis of randomized double blind placebo controlled studies, which presented that pre- and/or postnatal supplementation with Lactobacillus rhamnosus GG strain does not affect the occurrence of atopic dermatitis, and this strain should not be recommended in allergy prevention [ 61 ]. However, it is necessary to remember that probiotic effects are both strain- and population-specific.…”
Section: Infant Formulas Supplemented With Prebiotics and Probiotimentioning
confidence: 99%
“…These benefits emerged despite no difference in dropout rates between study arms, suggesting that Lactobacillus rhamnosus GG was well-tolerated and had no deleterious impact on health, consistent with past work. [87][88][89] Should these findings be replicated in larger and clinical samples including persons with diagnosed neurodegenerative and neuropsychiatric conditions, probiotic supplementation may ultimately prove to be a low-risk and cost-effective approach to promote cognitive health in older adults.…”
Section: Resultsmentioning
confidence: 99%